A ultima ceia do Doutor Fausto - Pimentel, Alberto, 1849-1925 (Salt Lake City, UT : Project Gutenberg, 2011)
"A ultima ceia do Doutor Fausto" by Alberto Pimentel is a narrative work that falls into the genre of fiction, likely written in the late 19th century. The novel explores themes of ambition, love, and the complexities of the human experience as embodied in the life of the protagonist, Doutor Filippe Sullivan, a distinguished physician reflecting on his illustrious yet solitary existence as he celebrates his seventieth birthday with a farewell dinner for close associates. The storyline centers around Doutor Filippe Sullivan, who is revered in society for his medical expertise but struggles with personal loneliness and unfulfilled romantic desires. As he hosts a gathering dubbed "his last supper," he decides to reveal his life story to his guests, sharing poignant reflections on his two great loves and the sacrifices he made in pursuit of glory and success. Sullivan's journey reveals the bittersweet nature of his achievements and the emotional void that accompanies his professional accolades, culminating in profound insights about love, ambition, and the inevitable approach of death. Through this narrative, Pimentel captures a rich tapestry of human emotions, ultimately asking the reader to contemplate the true meaning of fulfillment and connections in life. (This is an automatically generated summary.)
Release date is 2011-04-27
E-text prepared by Pedro Saborano
Keywords: Fiction